Un método de tratamiento para la mordida cruzada anterior en la dentición primaria - Hernández Silva , Jesús Alberto; Villavicencio Florez, Judy Elena (Revista Estomatología, 1997)
Early correction of anterior crossbite in primary dentition is important to avoid future damage to teeth, temporomandibular joint and suporting tissues. The use ofinclined plane is described. This technique is presented as successful treatment alternative in several case reports.